PENGARUH VARIASI KONSENTRASI EKSTRAK DAUN KANGKUNG DALAM SEDIAAN SAMPO TERHADAP PARAMETER SIFAT FISIK - Ariani, Yenni; Pranawati, Erma (Jurnal Riset Daerah, 2024)
Sampoo is one of the lotion preparations in cosmetics that can be used to clean hair and scalp. Water spinach leaf extract contains polyphenol, flavonoid and saponin compounds which act as antimicrobials. This study aims to determine the effect of variations concentration of water spinach leaf extract in anti-dandruff sampoo preparations on the pH value of homogeneity and foam height of the preparation as parameters for physical property tests. The manufacture of anti-dandruff sampoo from water spinach leaf extract uses a melting method with concentrations of water spinach leaf extract of 5%, 7.5% and 10%, respectively. Physical evaluation of the preparation includes pH test, Homogeneity test and foam height. Data analysis was tested statistically using ANOVA. The results of the physical property test showed that increasing the concentration of water spinach leaf extract in the sampoo preparation caused an increase in foam height, with a p value of 0.070 (P> 0.05), the same pH value for formulas 1, 2 and 3 (pH 6), and homogeneous for all formulas